PENDIDIKAN KESEHATAN NUTRISI IBU MENYUSUI ATAU POST PARTUM DI RS AN-NISA - Nuryani; Sulyanti Suhartini; Lutfiah Galuh Ayu; Hilda Nuramaliyah; Siti Homalia; Arum Arofiah Wiharti; Rahma Nurazizah; Eni Hermawati; Deva Restu Sari; Ratih Pisesa Pebriyanti; Ayu Dyah Faradina; Erna Susanti (Yayasan Nusantara Hasana Berdikari, 2023)
The postpartum period is a period between birth and the recovery of the reproductive organs back to their pre-pregnancy state, which lasts between 6-8 weeks. Inadequate nutritional management during the postpartum period can cause problems. The nutritional needs of postpartum mothers consist of 60-70% carbohydrates, 10-20% protein, and 20-30% fat. The mother's energy needs increase to 500-700 kcal, thus the mother must consume lots of foods that contain carbohydrates and high calories. Lack of knowledge of postpartum mothers about the importance of nutrition will cause problems, both for the mother and the baby. Health Education is needed to increase the understanding of post partum mothers regarding nutrition during post partum. Research objective to determine the effect of health education on the nutrition of breastfeeding mothers on the knowledge of post partum mothers. Research Methods: Health Education uses leaflets. The results of the study indicates that the knowledge of post partum mothers regarding the nutrition of breastfeeding mothers has increased to good knowledge after health education (100%). The conclusion from the research is that health education has an effect on increasing the knowledge of post partum mothers.